NEW PHARMACOLOGICAL APPROACHES IN THE TREATMENT OF ONCOLOGICAL DISEASES - Kaloyan D. Georgiev; Marieta Georgieva (Peytchinski Publishing, 2015)
Malignant diseases are significant and growing health problem in almost all countries of the world. Besides the results achieved in reduction of morbidity and mortality in individual countries, significant progress of science and practice of oncology medicine and the application of new methods of diagnosis and treatment, cancer remains the second leading cause of death after cardiovascular diseases. The past decade has seen breakthroughs in personalized cancer medicine, where new targeted therapies are being developed which inhibit cellular proliferation and survival in tumors with certain specific oncogenic mutations. These new treatment approaches have shown progress in the understanding of the origin and pathogenesis of tumors, and offer hope for a good outcome of neoplastic diseases. In this review the idea is to present up-to-date report on these new molecular mechanisms and to identify their advantages and disadvantages from the pharmacological point of view.